Living Isolated: Coping With COVID-19—Visual Self-Narrative Research. Issue 2 (3rd April 2022) - Kwesell, Allison; Rister, Alex; Nair, Shreya; Lin, Shuyang
Abstract : This article employs Folkman and Lazarus's Transactional Model of Stress and Coping utilizing the visual self-narrative methodology to explore participant experiences of isolation, uncertainty, and risk during the COVID-19 pandemic. Fifty-seven participants engaged in visual self-narrative and photo-elicitation workshops to understand coping during the pandemic and to examine implications of reflection on photographs. Findings from 878 photographs revealed that participants coped with COVID-19 and changed social environments more emotionally than behaviorally, likely because infection risk may feel out of one's control. Interestingly, when participants reflected on their own visual self-narratives, emotional coping continued to be more salient; the majority of participants felt a sense of overwhelming thankfulness for children, family, self, and time to spend with each.